Cytotoxicity of dental resin composites: an in vitro evaluation. Issue 6 (26th November 2011) - Ausiello, Pietro; Cassese, Angela; Miele, Claudia; Beguinot, Francesco; Garcia‐Godoy, Franklin; Jeso, Bruno Di; Ulianich, Luca
ABSTRACT Resin‐based dental restorative materials release residual monomers that may affect the vitality of pulp cells. The purpose of this study was to evaluate the cytotoxic effect of two light‐cured restorative materials with and without bis‐GMA resin, respectively (Clearfil Majesty Posterior and Clearfil Majesty Flow) and a self‐curing one (Clearfil DC Core Automix) when applied to the fibroblast cell line NIH‐3T3. Samples of the materials were light‐cured and placed directly in contact to cells for 24, 48, 72 and 96 h. Cytotoxicity was evaluated by measuring cell death by flow cytometry, cell proliferation by proliferation curves analysis and morphological changes by optical microscopy analysis. All the composite materials tested caused a decrease in cell proliferation, albeit at different degrees. However, only Clearfil DC Core Automix induced cell death, very likely by increasing apoptosis. Morphological alteration of treated cells was also evident, particularly in the Clearfil DC Core Automix‐treated cells. The different cytotoxic effects of dental composites should be considered when selecting an appropriate resin‐based dental restorative material for operative restorations. Copyright © 2011 John Wiley & Sons, Ltd.